Carbon Finance for Community Forestry : Notional or Reality ? - Dube, Lokesh Chandra; Sharma, J. v. V; Chatterjee, Sudipta (Indian Forester, 2021)
Small-scale forestry projects with carbon sequestration as primary aim have been developed and/or implemented by low-income communities on degraded land around the world. India has the highest number of such projects registered under the clean development mechanism (CDM) of the Kyoto Protocol. Ten small-scale Afforestation and Reforestation (AR) CDM projects are being implemented for ameliorating degraded lands by the state forest department with the help of communities through joint forest management activities in different forest divisions of Uttar Pradesh. Two of these projects located in Kashi and Mahoba forest divisions were studied to understand whether carbon finance is really a concern in overall project set-up and who is the real beneficiary of this promised revenue? Results indicated that even though the carbon finance is promised and is said to have a critical role in making the projects additional over business-as- usual, it does not influence the decisions and choices of the locals unless the benefits are really visible.